Plasmodium berghei: lactic acidosis and hypoglycaemia in a rodent model of severe malaria; effects of glucose, quinine, and dichloroacetate. - Holloway, P; Krishna, S; White, N (1991)
Fulminant malaria infections are characterised by hypoglycaemia and potentially lethal lactic acidosis. In young adult Wistar rats (n = 26) infected with Plasmodium berghei (ANKA strain), hyperparasitaemia (greater than 50%), anaemia (PCV 19.6 +/- 5.3%; mean +/- SD) hypoglycaemia (1.04 +/- 0.74 mmol/litre), hyperlactataemia (13.2 +/- 2.20 mmol/litre), hyperpyruvicaemia (0.51 +/- 0.12 mmol/litre) and metabolic acidosis (arterial pH 6.96 +/- 0.11) developed after approximately 14 days of infection. Hypoglycaemia was associated with appropriate suppression of plasma insulin concentrations. In a second series of experiments the metabolic effects of treatment with glucose (500 mg/kg/hr), quinine (5 mg/kg bolus followed by 10 mg/kg over 1 hr) and a potent activator of pyruvate dehydrogenase, dichloroacetate (300 mg/kg) were studied over a 1-hr period. In control animals quinine had no measurable effects, but dichloroacetate significantly reduced arterial blood lactate (74%) and pyruvate (80%). In infected animals, glucose infusion attenuated the rise in lactate (38% compared with 82%; P less than 0.01) but quinine had no additional metabolic effects. Dichloroacetate further attenuated the rise in lactate (14%; P less than 0.01).